Approaching intersectionality in gender psychology research - Sakka, Despina; Athanasiades, Christina (Psychology: the Journal of the Hellenic Psychological Society, 2023)
The present special section constitutes the first systematic attempt to present the concept of intersectionality in Greek psychological research and specifically in gender research. Consequently, it aims to highlight the ways in which gender intersects with other identificatory categories, shaping the experiences of individuals, especially those belonging to disadvantaged groups. The papers presented in the issue demonstrate that intersectionality reflects the reality of life while being at the same time, an important 'tool' for understanding the complexity of the human experience. It is expected that the special section will contribute, both at a research and clinical level, to a critical review of traditional theories and methods in Psychology, providing an impetus for further research which will take into consideration both cultural (e.g., social norms, stereotypes, etc.) and social (e.g., power structures) contexts in the study of individual behavior and experience.